Inequalities for some functions are related to the confluent hyper geometric function: Raed S. Batahan, Ayman Shehata - جامعة الأندلس للعلوم و التقنية, Raed S. Batahan, Ayman Shehata (مجلة الأندلس للعلوم التطبيقية, 2023)
This paper is motivated by an open problem of inequalities of confluent hypergeometric functions. Our goal is to derive some inequalities for error, incomplete gamma and Whittaker's functions. AMS Mathematics Subject Classification (2010) : 26D15 ; 30A10 ; 26D07.